Architectural Research in Hybrid Mode: Combining Diverse Methods within Design-Based Architectural Research Inquiry. Issue 1 (10th November 2021) - Zboinska, Malgorzata A.
With the rapid increase in architectural research activities over recent years, the repertoire of research methods has grown and matured. This essay takes a closer look at the methods that rely upon explorative design as the central activity of knowledge creation. Its first aim is to provide a comparative overview and critical examination of the available methodological typologies to enable their future development. The second aim of the essay is to employ these design-based methods to devise a framework for architectural research as a 'hybrid method'. This framework promotes the simultaneous application of differently composed amalgams of design-based research methods based upon analyses and insights taken from a specific architectural research project led by the author. The purpose of elaborating on the idea of the hybrid methodological mode is to help establish it as a part of the current repertoire of architectural research methods – today often framed from a 'mixed method' perspective that generally categorizes methodologies into either qualitative or quantitative. The essay proposes that the 'hybrid method' discussed herein covers a different typology of approaches, beyond this qualitative/quantitative distinction, and that its application in design-based research presents valuable opportunities for knowledge production and communication that should not be overlooked in the future development of architectural research methods.